Long-term characterization of air lime mortars with ceramic waste - Matias, Gina (2015)
Due to their exposure to environmental conditions, outer coatings composed by render and painting system are usually the first construction elements to deteriorate and require intervention. A correct conservation and rehabilitation of these materials is fundamental once they provide protection to other façade materials. It is known that old mortar renders were essentially air lime based mortars. To maintain the integrity of the whole wall-render elements, the image of the building and to avoid accelerated degradation, conservation and rehabilitation must be implemented with compatible mortars. As that, lime based mortars would be preferable. It was also common, in ancient renders, the incorporation of ceramic residues, which is, nowadays, an abundant material, especially in Central Region of Portugal. The reuse of these materials has great relevance once their landfilling causes serious environmental issues. In an attempt to combine the environmental and technical advantages of the use of ceramic waste in mortars’ production for rehabilitation purposes, a research has been developed at the University of Coimbra, in cooperation with Nova University of Lisbon, on the long term behaviour of air lime mortars with ceramic residues. In this paper the most significant up to one year results of an experimental campaign with air lime mortars with 1:3 and 1:2 volumetric proportions and ceramic residues are presented.